Wear measurement of dental tissues and materials in clinical studies: A systematic review. Issue 6 (June 2018) - Wulfman, C.; Koenig, V.; Mainjot, A.K.
Abstract: Objectives: This study aims to systematically review the different methods used for wear measurement of dental tissues and materials in clinical studies, their relevance and reliability in terms of accuracy and precision, and the performance of the different steps of the workflow taken independently. Methods: An exhaustive search of clinical studies related to wear of dental tissues and materials reporting a quantitative measurement method was conducted. MedLine, Embase, Scopus, Cochrane Library and Web of Science databases were used. Prospective studies, pilot studies and case series (>10 patients), as long as they contained a description of wear measurement methodology. Only studies published after 1995 were considered. Results: After duplicates' removal, 495 studies were identified, and 41 remained for quantitative analysis. Thirty-four described wear-measurement protocols, using digital profilometry and superimposition, whereas 7 used alternative protocols. A specific form was designed to analyze the risk of bias. The methods were described in terms of material analyzed; study design; device used for surface acquisition; matching software details and settings; type of analysis (vertical height-loss measurement vs volume loss measurement); type of area investigated (entire occlusal area or selective areas); and results. Sinificance: There is a need of standardization of clinical wear measurement. Current methods exhibit accuracy, which is not sufficient to monitor wear of restorative materials and tooth tissues. Their performance could be improved, notably limiting the use of replicas, using standardized calibration procedures and positive controls, optimizing the settings of scanners and matching softwares, and taking into account unusable data.